PERAN PERAWAT PADA BENCANA GEMPA BUMI DI CIANJUR - Ratu Dini; Siti Juleha Juleha; Fauzan Habibi Rahman Rahman (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
A disaster becomes an extraordinary event that disrupts and threatens life and livelihoods caused by nature and humans, or both. The existence of natural disasters can have both small and large impacts on the environment. The thing that can be done to reduce the consequences of disasters is that synergy from various parties is needed, one of which is the involvement of nurses. Nurses have a huge role to play in preparing and handling communities in the face of disasters. As health workers, nurses are at the forefront of disaster management so that they can anticipate the prevention of disasters and their impacts (Doondori, A. K., & Paschalia, Y. P. 2021). Cianjur Regency is one of the areas that experienced the impact of natural disasters, namely earthquakes. The earthquake occurred on November 21, 2022 at 13:21:10 WIB with a magnitude of 5.6 in the Cianjur area, West Java. The earthquake caused a lot of infrastructure damage and casualties. This has a great influence on the condition of the community, one of which is in terms of health biopsychosocially and spiritually. Based on the phenomenon that occurs along with the existence of the role of the nurse as a healthcare provider. Universitas Esa Unggul sent a team of health volunteers to carry out several activities for the community such as, providing comprehensive nursing services, becoming collaborators, conducting education and trauma healing. This action is considered sufficient to help patients who have health problems both who come to the post and who are in refugee tents. They feel happy because of the existence of health service facilities so that the public can consult, get education and also trauma healing.